MEMBACA DASAR-DASAR DAN IMPLEMENTASI FIKIH BUDAYA K.H. MA’RUF AMIN - Pujiono, Abdul Hamid (An Nawawi, 2021)
Cultural perceptions cannot be viewed as artistic perceptions. Often Indonesian society become talkative, when speaking culture is art. Though wide cultural coverage has placed the art on the portion that goes in it. Art is part of the culture. So the application and implementation of culture is basically daily and real. Integral and inseparable from human life. Therefore, the expression of art to stimulate creativity and innovation can not be equated with cultural perceptions that require harmony and harmony. Mapping the constellation of cultural fiqih will lead to socio-political realities in Indonesia. The concept of makharij al-fiqhiyyah initiated by K.H. Ma'ruf Amin will take the middle course. This is the answers to the existing reality, whether it involves understanding, movement, politics, or social imbalance. Islam through universal doctrine has given cultural outlines, but at the level of praxis still trapped in the past and outside influences. Keywords: culture fiqh, makharij al-fiqhiyyah